Distance Education for EFL Teachers: Perceptions of Learner Support (GIST – Education and Learning Research Journal, 2014)
This article reports the findings of a qualitative study exploring in-service EFL teachers’ perceptions of the learner support resources provided to them while they were taking a teacher research distance course. Findings indicate that students valued videoconferencing technology because it facilitated interacting with adviser, peers and instructor to get academic assistance, a different perspective on their work, enthusiasm, and feedback, as well as opportunities to confront ideas and to share feelings. The course management system was perceived as highly beneficial to their learning because of the amount and variety of support resources, and the multidimensional learning it promoted. Results may help language teacher educators interested in enhancing the quality of research courses, Web-based course developers involved in providing learner support, and researchers engaged in teacher research and distance education.
Keywords: Teacher education; distance learning; foreign languages; higher education; teaching